Uruguay - Strengthening Participatory Monitoring and Evaluation of Social Policy : Nonlending Technical Assistance Project, Report on Phase 2 - World Bank (Washington, DC, 2012)
The objectives of the Uruguay Nonlending Technical Assistance Project (UY NLTA) were to: (i) evaluate the impact of providing a safety net program's (PANES's) social emergency programs; (ii) inform a dialogue about the future role of social programs and of MIDES as a lead authority responsible for the coordination and oversight of social policy in Uruguay; and (iii) strengthen Ministry of Social Development's (MIDES's) capacity to assess, monitor, and evaluate social policy in Uruguay, with considerable weight given to participatory approaches to monitoring and evaluation. Expected outcomes of the project included: (a) increased efficiency in the implementation of Uruguay's social programs through the consolidation of existing and dispersed databases and the strengthening of MIDES's Monitoring and Evaluation (M&E) system; (b) increased transparency and strengthened accountability in selected departments through the piloting of a participatory monitoring and evaluation (PM&E) approach; (c) stronger engagement of civil society in public sector reform in Uruguay; and (d) informed decisions about the future of social programs under the Plan Nacional de Equidad, and the role of MIDES, on the basis of the evaluations of PANES. The rest of this report is organized as follows: section two presents the PSIA's main contribution by laying out the main results described in the technical note. Section three presents the Technical Assistance (TA) contribution and is divided into three subsections. Subsection one looks at the contributions to strengthen the capacity within MIDES to conduct impact analyses; subsection two analyzes activities in the TA aimed at making the M&E system operational; and subsection three describes the International Workshop on M&E. Section four describes the risks and main problems faced during the implementation of phase two and includes lessons learned, pending agenda, and next steps.